Measuring efficiency of automotive parts suppliers from entrepreneurial orientation by using data envelopment analysis - Moradi, Amir Hosein Deluyi (2015)
Entrepreneurship indices should be considered for measuring efficiency in parallel with rapid growth in manufacturing technology industry. However, in Iran, automotive industries lack entrepreneurship and effective methods for measuring efficiency. To address the problem, the study has three main aims: firstly, to examine the relationship between enabler factors of entrepreneurial orientation and entrepreneurial orientation of automotive parts suppliers, secondly, to rank and identify inefficient suppliers through measuring efficiency from an entrepreneurial orientation perspective, and finally, to find ways to improve inefficient suppliers. This study applied both quantitative and qualitative approaches. In the quantitative phase, 422 out of 510 sets of questionnaire focusing on enabler factors of entrepreneurial orientation and entrepreneurial orientation were collected from middle and lower managers as well as technicians of 51 Iranian automotive parts supplier firms. SPSS was used to statistically analyze data and data envelopment analysis method was applied specifically to measure efficiency. The results revealed that two (structure and policy) out of six enabler factors of entrepreneurial orientation, were not significant predictors of entrepreneurial orientation. Scores of efficiency indicated that16 of these firms were inefficient from an entrepreneurial orientation viewpoint. The data envelopment analysis not only showed the inefficient suppliers but also revealed quantitative suggestions. Besides that, qualitative data collection based on open-ended questionnaires to seek the opinions of nine industry and entrepreneurship experts were carried out. Based on the findings, it is suggested that attention be drawn to the components of entrepreneurial orientation, namely innovation, risk-taking, pro-activeness, autonomy, competitive and aggressiveness. They have roles with various degrees of importance in entrepreneurship and consequently in the improvement of efficiency score of inefficient suppliers. Recommendations based on data envelopment analysis and experts’ opinions to improve the efficiency of the inefficient firms have been made in the study by suggesting ways to eliminate inefficiency due to lack of entrepreneurial orientation among suppliers.